Advances and challenges in paracoccidioidomycosis serology caused by Paracoccidioides species complex: an update - Silva, Julhiany de Fátima da [UNESP]; Oliveira, Haroldo Cesar de [UNESP]; Marcos, Caroline Maria [UNESP]; Assato, Patricia Akemi [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Elsevier B. V., 2015)
Understanding the possible methodologies for the rapid and inexpensive identification of fungal infections is essential for disease diagnosis, but there are some limitations. To help with this problem, serological methods that detect antigens or antibodies are widely used and are useful for the diagnosis of paracoccidioidomycosis (PCM) through the detection of gp43, which is the main antigen employed for the immunodiagnosis of this disease caused by Paracoccidioides brasiliensis. However, the use of gp43 has become restricted because it was recently found that this marker is not identified in the infections caused by Paracoccidioides lutzii. Therefore, it is necessary to identify new antigens in both species or antigens specific for P. lutzii to decrease the morbidity and/or mortality associated with PCM. This review provides a discussion of new diagnostic challenges after the recent discoveries regarding the taxonomy of the Paracoccidioides genus.
Keywords: Immunodiagnosis; Paracoccidioides spp; Paracoccidioidomycosis; Serology